Theoretical study of structural stability, elastic, electronic and thermodynamic properties of ScxGa1−x P compounds by ab initio calculations (2016)
We carried out a theoretical study on the structural stability, elastic, electronic and thermodynamic properties of the ScxGa1 x P compound (x ¼ 0, 0.25, 0.50, 0.75 and 1) in the ZnS and NaCl crystallographic phases. For this purpose, we performed ab initio calculations using the DFT within LDA and GGA approximations. To solve the Kohn-Sham equations, we implemented the accurate full-potential linearized augmented plane wave method. From the results obtained, it can be noted that for the 0x0.30 range, the most stable structure of ScxGa1 x P is the ZnS phase, and for the 0.30<x1 interval, the most stable structure is the NaCl phase. The structural results also show a phase transition from the ZnS to NaCl at a pressure of ~ 2.84 GPa for a Sc concentration value of 25%. Electronic band structure analysis shows that in the ZnS phase, for a 25% of Sc concentration, ScxGa1 x P is a direct semiconductor, and from 50% to 100% concentrations in the NaCl phase, the compound exhibits a metallic behavior. Calculated phase diagrams predict ScxGa1 x P to be stable as homogeneous alloy phases at high temperature for both ZnS and NaCl phases